Developments in the narrow money supply (M1) and its effects on the Iraqi economy for the period (2010-2023) - Assistant teacher. Jamal Tariq Muhammad Sabry*; Assistant Prof. Fadhel Jawad Dahash (مجلة الدراسات الاقتصادية والادارية)
This research dealt with the timeline of the development of the narrow money supply M1 in Iraq (2010-2023) in terms of size, components, and factors affecting it. The research relied on the descriptive analytical method in its methodology in reviewing the developments of the money supply during that period. The research concluded that the structure of the money supply in Iraq tends in favor of the currency in circulation during the research period and that the development of the money supply is mainly linked to the changes in the oil revenues achieved as the main financier of the state's general budget. The research recommended the necessity of adopting appropriate monetary and financial policies aimed at controlling the size of the money supply in the Iraqi economy.